Penerapan Asas First to File sebagai Perlindungan Hukum Merek dalam Sengketa TikTok Ltd vs Fenfiana Saputra - Panjaitan, Putri Tamara (WELFARE STATE Jurnal Hukum, 2025)
The rapid development of science and technology encourages the improvement of various intellectual works, including trademarks, which have strategic value in the business world. In Indonesia, the legal protection of trademarks is regulated in Law Number 20 Year 2016 on Trademarks and Geographical Indications which adheres to the *first to file* principle, which gives exclusive rights to the party who first registers the trademark. This research aims to analyze the application of the *first to file* principle in the trademark legal protection system in Indonesia through a case study of the dispute between TikTok Ltd and Fenfiana Saputra. The method used is normative legal research with an analytical descriptive approach, using secondary data in the form of laws and regulations, court decision documents, and related legal literature. The results show that the *first to file* principle emphasizes the importance of registration as a basis for legal protection. In this case, the early registration by Fenfiana Saputra in class 25 provides valid legal rights even though TikTok Ltd is the owner of a globally famous mark.